Assessment Using AutoCAD Software of the Preparation of Dentin Walls in Root Canals Produced by 4 Different Endodontic Instrument Systems. (18th November 2015) - Cabanillas, Cristina; Monterde, Manuel; Pallarés, Antonio; Aranda, Susana; Montes, Raquel
Abstract : Objectives . To compare the effectiveness of four instrument systems for preparing oval root canals: manual instrumentation (Step-Back technique), ProTaper Universal, ProTaper Next, and Wave One. Material and Methods . For the purpose of this assessment, 60 teeth extracted for orthodontic or periodontal reasons, specifically canines and premolars with full coronal and root anatomy, were used and 15 samples were assigned to each group. The section of the canals was compared before and after instrumenting and the section of untouched canal wall was measured using AutoCAD software. The data was analysed by means of Shapiro-Wilk, ANOVA, and Kruskal-Wallis tests. Results . In the apical third, 100% of the canals were prepared with all the systems. In the middle third, ap value of 0.5989 in the Kruskal-Wallis test was obtained, which indicates no significant difference between the groups. At the coronal third level, the results obtained revealed that Wave One had a significantly lower mean average than the rest (p < 0.05 ). Conclusions . There are no differences between the various root canal instrument systems in the apical and middle thirds. At the coronal third level, Wave One system showed performance significantly worse than the rest, among which there were no differences.